Rice genetics V proceedings of the Fifth International Rice Genetics Symposium, the Philippines, 19-23 November 2005 - Brar, Darshan S.; Mackill, David J.; Hardy, Bill (World Scientific Publishing, 2005)
The Rice Genetics Collection of past symposia and other selected literature contains nearly 4,400 pages of searchable information on rice genetics and cytogenetics published by the IRRI and its partners since 1964. In addition to the five genetics symposia held at 5-year intervals since 1985, the collection contains classic publications that kicked off significant reporting on these subjects in the early 1960s. This collection is a comprehensive and historical documentation on the subject of rice genetics, spanning 45 years of research and scholarly work.